The genomic landscape of pancreatic and periampullary adenocarcinoma - Sandhu, V; Wedge, D; Bowitz Lothe, I; Labori, K; Dentro, S; Buanes, T; Skrede, M; Dalsgaard, A; Munthe, E; Myklebost, O; Lingjærde, O; Børresen-Dale, A; et al. (American Association for Cancer Research, 2016)
Despite advances in diagnostics, less than 5% of patients with periampullary tumors experience an overall survival of five years or more. Periampullary tumors are neoplasms that arise in the vicinity of the ampulla of Vater, an enlargement of liver and pancreas ducts where they join and enter the small intestine. In this study, we analyzed copy number aberrations using Affymetrix SNP 6.0 arrays in 60 periampullary adenocarcinomas from Oslo University Hospital to identify genome-wide copy number aberrations, putative driver genes, deregulated pathways, and potential prognostic markers. Results were validated in a separate cohort derived from The Cancer Genome Atlas Consortium (n = 127). In contrast to many other solid tumors, periampullary adenocarcinomas exhibited more frequent genomic deletions than gains. Genes in the frequently codeleted region 17p13 and 18q21/22 were associated with cell cycle, apoptosis, and p53 and Wnt signaling. By integrating genomics and transcriptomics data from the same patients, we identified CCNE1 and ERBB2 as candidate driver genes. Morphologic subtypes of periampullary adenocarcinomas (i.e., pancreatobiliary or intestinal) harbor many common genomic aberrations. However, gain of 13q and 3q, and deletions of 5q were found specific to the intestinal subtype. Our study also implicated the use of the PAM50 classifier in identifying a subgroup of patients with a high proliferation rate, which had impaired survival. Furthermore, gain of 18p11 (18p11.21-23, 18p11.31-32) and 19q13 (19q13.2, 19q13.31-32) and subsequent overexpression of the genes in these loci were associated with impaired survival. Our work identifies potential prognostic markers for periampullary tumors, the genetic characterization of which has lagged. Cancer Res; 76(17); 5092-102. ©2016 AACR.